Evaluation of Novel Scoring System Named 5-5-5 Exacerbation Grading Scale for Allergic Conjunctivitis Disease - Shoji, Jun; Inada, Noriko; Sawa, Mitsuru (Allergology international, 2009)
Background: The objective of this study is to evaluate the practical usefulness of a scoring system using the 5-5-5 exacerbation grading scale for allergic conjunctivitis disease (ACD). Methods: Subjects were 103 patients with ACD including 40 patients with vernal keratoconjunctivitis (VKC), 20 patients with atopic keratoconjunctivitis (AKC), and 43 patients with allergic conjunctivitis (AC). The 5-5-5 exacerbation grading scale consists of the following 3 graded groups of clinical observations: the 100-point-grade group (100 points for each observation) includes active giant papillae, gelatinous infiltrates of the limbus, exfoliative epithelial keratopathy, shield ulcer and papillary proliferation at lower palpebral conjunctiva; the 10-point-grade group (10 points for each observation) includes blepharitis, papillary proliferation with velvety appearance, Horner-Trantas spots, edema of bulbal conjunctiva, and superficial punctate keratopathy; and the 1-point-grade group (1 point for each observation) includes papillae at upper palpebral conjunctiva, follicular lesion at lower palpebral conjunctiva, hyperemia of palpebral conjunctiva, hyperemia of bulbal conjunctiva, and lacrimal effusion. The total points in each grade group were determined as the severity score of the 55–5 exacerbation grading scale. Results: The median severity scores of the 5-5-5 exacerbation grading scale in VKC, AKC and AC were 243 (range: 12–444), 32.5 (11–344), and 13 (2–33), respectively. The severity score of each ACD disease type was significantly different (P<0.001, Kruskal-Wallis test). The severity of each type of ACD was classified as severe, moderate, or mild according to the severity score. Conclusions: The 5-5-5 exacerbation grading scale is a useful clinical tool for grading the severity of each type of ACD.